The first Hebrew newspapers in Europe. Economic and Organizational Aspects - Kouts, Gideon (Historia y Comunicación Social, 2003)
The article describes the characteristics of the Hebrew press published in Europe in the second half of the XIXth century, as well as its special economic and organizational aspects. Although the Hebrew press emerged at the time of technological advances in printing, financial problems and the circulation limitation imposed by its linguistic distinctiveness were obstacles to success. Individual efforts of entrepreneurs and journalists had to mark step by step the way to modernization.